Analisis Polimorfisme Padi Varietas Lokal Sumatera Selatan Berdasarkan Pendekatan PCR-RAPD - Fikri Adriansyah; Laila Hanum; Muharni Muharni; Yuanita Windusari (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Adriansyah et al, 2018. Polymorphism Analysis of Local Varieties of South Sumatra Rice Based on PCR-RAPD. JLSO 7(1):50-58.The existence of rice germplasm is threatened because of the introduction of various high-yielding varieties. This study aimed to analyze rice kinship and conservation of local varieties of South Sumatra rice. This study was conducted in August 2015 to December 2015. DNA isolation using the Promega Wizard Purification Systems KIT. This study uses OPA-9 primer, OPA-10, OPA-13, OPA-16. All primers can amplify DNA with optimal quality. OPA-9 primers produced 5 DNA bands, OPA-10 primers produced 9 DNA bands, OPA-13 primers produced 12 DNA and Primary OPA-16 bands producing 9 ppita DNA.